Facial image protection based on watermarking technique - Kiung, Siew Lian; Liew, Siau-Chuin (2021)
Facial Image with Tamper Localization and Lossless Recovery. Automatically calculate the PSNR value & MSE value of watermarked facial images. Recovered the tampered watermarked facial image to its original image without decrease fidelity of the facial image.